2023
DOI: 10.3389/fsurg.2023.1083961
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bilateral nasal packing on sleep oxygen saturation after general anesthesia: A prospective cohort study

Abstract: ObjectiveThis study aims to evaluate the effect of bilateral nasal packing on sleep oxygen saturation and its influencing factors on the first night after general anesthesia.MethodA total of 36 adult patients who underwent bilateral nasal packing with a nonabsorbable expanding sponge after general anesthesia surgery were prospectively studied. All these patients underwent overnight oximetry tests before and the first night after surgery. The following oximetry variables were collected for analysis: the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…We also compared our results with past research in the literature. Guan et al found that bilateral nasal packing could cause sleep hypoxemia, which aligns with the results of our study, and patients with bilateral nasal packing had significantly low SpO2 levels postoperatively [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also compared our results with past research in the literature. Guan et al found that bilateral nasal packing could cause sleep hypoxemia, which aligns with the results of our study, and patients with bilateral nasal packing had significantly low SpO2 levels postoperatively [11].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 56 (67.5%) patients were male, while 27 (32.5%) of the patients were female. The mean age of the participants was 27.65 years, and these demographics are comparable to previously conducted studies [11][12][13][14][15][16]. The most common surgery for which nasal packing was performed for patients in our study was septoplasty, which matches the findings of other past studies [12,17].…”
Section: Discussionsupporting
confidence: 89%